A Description of the nymph of Anacroneuria ofaye (Plecoptera: Perlidae) and a rearing apparatus for rearing Neotropical stonefly species - Novaes, Marcos Carneiro [UNESP]; Bispo, Pitágoras da Conceição [UNESP]; Higuti, Janet (My University, 2012)
The Neotropical genus Anacroneuria (Perlidae) is represented by more than 300 species. Among the Brazilian Anacroneuria, only the nymphs of two species have been described. In this paper, we described the nymph of A. ofaye Froehlich and an apparatus for rearing this genus. This is the first record of A. ofaye from Paraná State, Brazil.

O gênero neotropical Anacroneuria (Perlidae) é representado por mais de 300 espécies. Entre os Anacroneuria brasileiros, apenas as ninfas de duas espécies foram descritas. Neste trabalho, descrevemos a ninfa de A. ofaye Froehlich e um aparato para criação deste gênero. Este é o primeiro registro de A. ofaye no Estado do Paraná, Brasil.
Keywords: Plecoptera; Anacroneuria; Nymph; Rearing apparatus; Brazil; Plecoptera; Anacroneuria; |Ninfa; Aparato de criação; Brasil